Utilization of Lignin and Lignosulfonate from Oil Palm Empty Fruit Bunches as Filler in PVDF Proton Exchange Membrane Fuel Cell - Nala Ridhwanul Mu'izzah; Pinka Zuhdiana Hapsari; Nabila Putri Aulia; Dian Wahyu Tri Wulansari; Fauziyah Azhari; Edi Pramono (Universitas Gadjah Mada, 2023)
A study on the polyvinylidene fluoride (PVDF) membrane using lignin and lignosulfonate oil palm empty fruit bunch (OPEFB) fillers have been carried out. This study aims to determine the additional effect of lignin and lignosulfonate on PVDF membrane. Lignin sulfonation has a good result proven by Fourier transform infrared spectra with a peak at 1192 cm−1 which indicates sulfonate group. The sulfonation degree was increased by 8.9% for lignosulfonate. The membrane was prepared by the phase inversion method. Data present that all the membranes have an asymmetric structure with finger-like and sponge-like pores. Good thermal stability indicated by thermal gravimetric analysis showed degradation at 432 °C. The mechanical properties of the membrane decrease with the addition of filler. From the X-ray diffraction, peaks appeared at 18.39°, 21.35°, and 23.75° for all the membranes indicating of α and β phases. Lignin and lignosulfonate increased membrane hydrophilicity and water uptake. The presence of the sulfonate group increases the ionic exchange capacity and ionic conductivity up to 2.78 mmol/g and 9.95 × 10−5 S/cm, respectively, for 5% lignosulfonate addition. Thus, PVDF/lignosulfonate has the potential as a polymer electrolyte membrane.